Speaker discrimination as a function of vowel realization: does focus affect perception? - Heeren, Willemijn; Voeten, Cesko; Marks, Tessi (Dutch Journal of Applied Linguistics, 2022)
The acoustic-phonetic characteristics of speech sounds are influenced by their linguistic position in the syllable or sentence. Because of acoustic-phonetic differences between different speech sounds, sounds vary in the amount of speaker information they contain. However, do spectral and durational differences between realizations of the same sound that were sampled from different linguistic positions also impact speaker information? We investigated speaker discrimination in [−focus] versus [+focus] word realizations. Twenty-one Dutch listeners participated in a same-different task, using stimuli varying in focus, vowel ([aː], [u]), and word context ([ɦ_k], [v_t]), spoken by 11 different speakers. Results showed that an effect of focus on speaker-dependent information was present, but limited to words containing [u]. Moreover, performance on [u] words was influenced by (interactions of) word context and trial type (same-vs. different-speaker). Context-dependent changes in a speech sound’s acoustics may affect its speaker-dependent information, albeit under specific conditions only.